Perbandingan Return Investasi Emas Dan Investasi Saham (Capital Gain) PT. Aneka Tambang Tbk Pada Periode Januari 2019 – April 2020 - Ivo Vera Wahyu Ningsih; Sugiharto Sugiharto; Setio Utomo (Smart Business Journal, 2021)
This study aims to determine the comparison between the return on investment in gold and return on investment in stocks at PT. Aneka Tambang Tbk in the period January 2019 - April 2020. This research is a descriptive comparative study with a quantitative approach. The data used are secondary data. Data collection techniques using documentation and literature study. While the data analysis technique used the Independent Samples T-Test. Based on the results of tests that have been carried out regarding the comparison of Return on Gold Investment and Return on stock Investment (capital gain) at PT. Aneka Tambang Tbk for the period January 2019 – April 2020, information is obtained that there is a difference in profit which is more profitable is investing in gold in the short term with an average return value of gold which is 2.2925% greater than the average value of stock return, namely -1.4931% and there is no significant difference if investing in the long term between Return on Gold Investment and Return on Stock Investment (capital gain) at PT. Aneka Tambang Tbk Periode January 2019 – April 2020 with a probability level (sig 2-tailed) 0.306 > 0.05. The result of the research on the Independent Sampel T-Test prove that there is no significant difference between Return on Gold Investment and Return on Stock Investment at PT. Aneka Tambang Tbk with a significant value of 0.306 or in other word Ha is rejected and Ho accepted. Keywords:  Return, Investment, Gold, StockPerbandingan Return Investasi Emas Dan Investasi Saham (Capital Gain) PT. Aneka Tambang Tbk Pada Periode Januari 2019 – April 2020